The Rice Diacylglycerol Kinase Family: Functional Analysis Using Transient RNA Interference - Ge, Hongliang; Chen, Chu; Jing, Wen; Zhang, Qun; Wang, Hong; Wang, Rong; Zhang, Wenhua (Frontiers in Plant Science, 2012)
Diacylglycerol kinase (DGK) is a pivotal enzyme that phosphorylates diacylglycerol (DAG) to form phosphatidic acid (PA). The production of PA from phospholipase D (PLD) and the coupled phospholipase C (PLC)/DGK route is an important signaling process in animal and plant cells. In this study, we report a genomic analysis of eight putative rice DGKs encoded by a gene family (OsDGKs) grouped into three clusters. To further investigate the functions of the OsDGKs, a double-stranded RNA (dsRNA)-induced RNA silencing method was established. Introduction of in vitro-synthesized dsRNAs corresponding to a unique or conserved region of OsDGKs into rice protoplasts abolished or diminished the expression of individual or multiple OsDGK genes. Suppressing the expression of OsDGKs resulted in a distinct depletion of the transcripts of the defense gene OsNPR1 and the salt-responsive gene OsCIPK15. Our primary results suggest that OsDGKs are involved in the signaling of stress responses.